The Big Catch-up: Addressing Zero-Dose Children as a Surrogate of Vaccination Disruptions During Public Health Emergencies: A review of literature - Khan, Sadaf; Gupta, Gajendra Kumar; Agrawal, Deepika; Nawaz Zaidi, Syed Hasan; Batra, Jyoti; Syed, Sabin; Sharma, Lokesh; Khambira, Maureen; Haile, Dereje Ayalew; Sethy, Ghanshyam; Singh, Snehil Kumar (European Scientific Journal, ESJ, 2024)
The COVID-19 pandemic triggered an unprecedented backslide in global immunization programs, increasing the number of zero-dose children-those who have not received any vaccinations—from 13.3 million in 2019 to 18.1 million in 2021. This surge poses a significant threat to public health, especially in low- and middle-income countries (LMICs), where healthcare systems are already fragile. This scoping review focused on the impact of the pandemic on childhood immunization, with a focus on zero-dose children, and to identify effective interventions for rebuilding resilient immunization systems. Data from WHO, UNICEF, and Gavi were comprehensively reviewed. The IRMMA (Identify, Reach, Monitor, Measure, Advocate) framework was used to structure the analysis of evidence-based interventions across diverse settings. Consolidated findings show that in 2022, 20.5 million children missed one or more vaccines, with 14.3 million classified as zero-dose children. Despite improvements from 2021, these numbers remain higher than pre-pandemic levels. Countries such as Nigeria (2.3 million zero-dose children), India (1.1 million), and Ethiopia (1.1 million) are most affected. Our review highlights the importance of strengthening health systems and leveraging innovative strategies such as drone delivery and digital health platforms for reaching zero-dose children. To ensure sustainability, policy interventions must focus on integrating immunization efforts into national healthcare frameworks. This includes prioritizing workforce development, enhancing supply chain management, and fostering partnerships with community leaders to rebuild trust and address vaccine hesitancy. Specific interventions, such as deploying mobile vaccination units, implementing culturally tailored health messaging, and utilizing real-time monitoring technologies, are recommended to target under-reached populations. The pandemic has exacerbated existing vulnerabilities in immunization systems but coordinated global efforts, like the "Big Catch-Up" campaign, offer a pathway to recovery and long-term sustainability. This scoping review underscores the urgent need for robust, context-specific policies and targeted interventions to bridge the immunization gap and protect vulnerable populations from vaccine-preventable diseases.